Using FPGA Design and HIL Algorithm Simulation to Control Visual Servoing - Lway Faisal Abdulrazak; Zaid A. Aljawary (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
This is a novel research paper provides an optimal solution for object tracking using visual servoing control system with programmable gate array technology to realize the visual controller. The controller takes in account the robot dynamics to generate the joint torques directly for performing the tasks related to object tracking using visual servoing. Also, the notion of dynamic perceptibility provides the capability of the designed system to track desired objects employing direct visual servoing technique. This idea is assimilated in the suggested controller and realized in the programmable gate array. Additionally, this paper grants an ideal control framework for direct visual servoing robots that incorporates dynamic perceptibility features. With the aim of evaluating the proposed FPGA based architecture, the control algorithm is applied to Hardware-in-the-loop simulation (HIL) set up of three degrees of freedom rigid robotic manipulator with three links. Furthermore, different investigations are performed to demonstrate the behavior of the proposed system when a trajectory adjacent to a singularity is attained.